The normal cell proliferation and wound healing effect of polysaccharides from Ganoderma amboinense - Shuangzhi Zhao; Ming Lei; Hui Xu; Hailun He; Alexander Suvorov; Junhua Wang; Jiying Qiu; Qingxin Zhou; Jinyu Yang; Leilei Chen (Food Science and Human Wellness)
To study the cell proliferation and wound healing activity of polysaccharides from Ganoderma amboinense (GAMPS), the polysaccharide was extracted by water extraction and alcohol precipitation method, and its monosaccharide composition and molecular weight were analyzed. The effects of different concentrations of GAMPS on the cell proliferation were determined by cell survival rate test, and the wound healing ability of GAMPS to NIH/3T3 cells was detected. The preliminary evaluation of the antioxidant ability of GAMPS was conducted by the oxygen radical absorbance capacity (ORAC). The results showed that the GAMPS was composed of glucose, mannose, and galactose at a molar ratio of 67.62:14.07:7.50, and the weight-average molecular weights were 5.439 × 106 and 1.704 × 105 g/mol by using high-performance gel-permeation chromatography-multiple angle laser scatter (HPGPC-MALS) analysis. GAMPS (0.2 μg/μL) showed the strongest proliferation ability to THP-1 cells, with cell survival rate of 178.7%. The wound healing effect of GAMPS (0.1 μg/μL) was obvious on NIH/3T3 and 3.75 μg/μL of GAMPS showed the strongest total antioxidant ability. All the results indicate that GAMPS promotes cell proliferation, and has cell wound healing effect and strong antioxidant activity. The results provide theoretical foundation for the development and utilization of GAMPS.